2020
DOI: 10.1002/cpp.2489
|View full text |Cite
|
Sign up to set email alerts
|

A single case series using visuospatial task interference to reduce the number of visual intrusive memories of trauma with refugees

Abstract: The current worldwide so‐called "refugee crisis" has led to an unprecedented increase in migration globally. Because of stigma and language barriers, mental health care for refugees is limited. There is a need for novel, scalable psychological interventions. We investigated whether a brief behavioural intervention involving a memory reminder cue and Tetris gameplay on a smartphone reduces intrusive memories in refugees using a single case (N = 4) ABAB withdrawal design. The baseline phase (A) included a no‐int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Moving from the laboratory to clinical settings with individuals exposed to real trauma, accruing preliminary evidence suggests the intervention may reduce the occurrence of intrusive memories both when recently acquired 3,26 and longstanding (consolidated) [27][28][29] . For example, women who completed the intervention soon after traumatic childbirth (6 h after an emergency caesarean section in a Swiss hospital) reported fewer intrusive memories (by 48%) in the subsequent week relative to the (usual care) control condition 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Moving from the laboratory to clinical settings with individuals exposed to real trauma, accruing preliminary evidence suggests the intervention may reduce the occurrence of intrusive memories both when recently acquired 3,26 and longstanding (consolidated) [27][28][29] . For example, women who completed the intervention soon after traumatic childbirth (6 h after an emergency caesarean section in a Swiss hospital) reported fewer intrusive memories (by 48%) in the subsequent week relative to the (usual care) control condition 26 .…”
Section: Introductionmentioning
confidence: 99%
“…First, having even a brief but sudden and unplanned lapse in concentration after an intrusion can have the potential to interfere with the type of work-related duties that require focused attention, such as monitoring patients who are critically ill on a respirator. In our previous work, we have seen indication that intrusive memories can have a significant impact on people's perception of their ability to concentrate [7,32]. Second, when the content of intrusive memories is of work-related traumatic events (eg, a difficult resuscitation, a typical situation reported by nurses as cause for intrusions [12]), the triggers for these intrusions are typically in work-related environments.…”
Section: Summary Of Findingsmentioning
confidence: 97%
“…In a study with patients with more diverse trauma types in a Swedish emergency department, participants in the intervention condition reported 48% fewer intrusive memories compared to attention placebo control at week 1 following the intervention and 90% fewer at week 5 [28]. Promising results in terms of established intrusion reductions have also been shown in small-scale case series research with refugees [32], patients with complex PTSD [31], and in a person with bipolar disorder and PTSD [33].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary studies, following real-life trauma, showed moderate effect sizes on intrusive memory frequency in the first week post-trauma after visuo-spatial tasks (e.g., Cohen's d of 0.65 in Horsch et al, 2017 ; Cohen's d of 0.67 in Iyadurai et al, 2018 ). This approach was used in several contexts of trauma, i.e, after a car accident ( Iyadurai et al, 2018 ) or in traumatised refugees ( Kanstrup et al, 2020 ). For instance, Tetris use ( Fig.…”
Section: Introductionmentioning
confidence: 99%